1997
DOI: 10.1046/j.1365-2567.1997.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibits the secretion of T‐helper 1‐ and T‐helper 2‐associated cytokines in activated human T cells‘pa

Abstract: SUMMARYMechanisms regulating the balance of T-helper 1 ( Th1) and T-helper 2 ( Th2) immune responses are of great interest as they may determine the outcome of allergic and infectious diseases. Recently, in mice, nitric oxide ( NO), a powerful modulator of inflammation, has been reported to preferentially down-regulate Th1-mediated immune responses. In the present study, we investigated the effect of NO on the production of Th1-and Th2-associated cytokines by activated human T cells and human T-cell clones. Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
3
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 25 publications
5
66
3
2
Order By: Relevance
“…Thus, we are unable to concur with the hypothesis that NO amplifies Th2 responses in humans and that this may underlie IgE-mediated diseases such as asthma (23). In this respect, our results agree more closely with those of Bauer et al (25).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Thus, we are unable to concur with the hypothesis that NO amplifies Th2 responses in humans and that this may underlie IgE-mediated diseases such as asthma (23). In this respect, our results agree more closely with those of Bauer et al (25).…”
Section: Discussioncontrasting
confidence: 76%
“…For example, one group has claimed that NO selectively inhibits cytokine production by murine Th1 vs Th2 cell clones and has hypothesized that NO may promote Th2 responses in mice and humans (21)(22)(23). Contradictory studies reported that NO inhibits proliferation of cloned mouse Th1 and Th2 cells equally without inhibiting IFN-␥, IL-4, or IL-5 release (24) or that NO inhibits release of both Th1 and Th2 type cytokines from activated human T cells (25). Further studies claimed that the antiproliferative effect of NO on human T cells is not associated with changes in IL-2 production but rather is cytostatic at a later stage of the growth cycle (16,26).…”
mentioning
confidence: 99%
“…In fact, lowering of cAMP levels by induction of phosphodiesterase-7 was reported to be required for T cell activation (14). Nitric oxide, which activates soluble guanylate cyclase and increases intracellular cGMP, has inhibitory effects on T cell proliferation (15) and cytokine secretion (16), stimulates c-Jun Nterminal kinase, ERK, and p38 activities in Jurkat T cells (17), and decreases tyrosine phosphorylation of Jak3/STAT5 and proliferation in cultured T cells (18). However, NO can elicit effects via both cGMP-dependent and -independent pathways, and increasing intracellular cGMP may affect not only cGMP-dependent protein kinase but also cGMP-regulated phosphodiesterases or channels and cAMP-dependent protein kinase (19,20).…”
Section: ⅐Cd3mentioning
confidence: 99%
“…Abnormal regulation of 5-HT in the gut has been implicated in some GI disorders, including inflammatory bowel disease (Magro et al 2002;Coates et al 2004). Similarly, TNF is a proinflammatory cytokine that is involved in the pathogenesis of gastric ulcers; it can cause apoptosis of gastric parietal cells (Neu et al 2003) and act as an inhibitor of constitutive nitric oxide synthase (cNOS) (Bauer et al 1997). This is important in that this could lead to reductions in local levels of NO, a vasodilator that maintains adequate blood flow to gastric mucosa (Pique et al 1989).…”
Section: Introductionmentioning
confidence: 99%